(untitled) (World Bulletin of Public Health, 2021)
Recent World Health Organization reports put much emphasis on the issue of bacterial resistance to antibiotic therapy. Multi-drug resistance (MDR) has prompted researchers for alternative to monotheraputic approach by introducing nanotechnology that involve in their diverse sense – materials (metals / metal oxides), synthesis (organic / phytogenic) and synergistic dynamical interaction. Toxicity in host cells emerged as limitation to this approach. Green nanotechnology with the ease of employment is hoped to be less toxic but need to be researched further with emphasis on in-vivo arena to gain acceptability. This review is intended to shed a light on MDR organisms and elimination strategies and current approaches of nanotechnologies that are utilized in the path to eradicate MDR especially the combinational therapy of synthetic or green NPs with antibiotics